Efektifitas Pelaksanaan Kelas Ibu Hamil terhadap Peningkatan Pengetahuan dan Sikap Ibu Hamil tentang Deteksi Dini Risiko Tinggi di Puskesmas Lalowaru Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara - Aswita Aswita; Hasmia Naningsi; Hendra Yulita (Health Information : Jurnal Penelitian, 2019)
Maternal and child health is the third SDG target, which is to ensure a healthy life and promote welfare for all people of all ages. The class of pregnant women is part of the Maternal and Child Health Program that has been implemented since 2009. The purpose of this study is to assess the effectiveness of the implementation of the class of pregnant women on the knowledge and attitudes of early detection of high risk factors in the Lalowaru Health Center, Konawe Selatan Regency. The method in this study used a quasi-experimental. The treatment group was given intervention in the form of education using a pocket book for 6 months (starting from the second trimester of pregnancy to the third trimester of pregnancy). The control group did not receive education and pocket books. The research sample consisted of 40 respondents consisting of the intervention group of 20 people and the control group of 20 people. Data analysis used the Wilcoxon signed test. The results showed that education increased the knowledge of pregnant women about early detection of pregnancy (mean posttest in the intervention group: 92.69 ± 0.96 (p-value = 0.000)). Education improves the attitudes of pregnant women about early detection of pregnancy (mean posttest intervention: 96.36 ± 0.84 (p-value = 0.000)). Education increases ANC visits for pregnant women about early detection of pregnancy.